2022
DOI: 10.3390/w14203290
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flow Modeling for Bed Erosion by a Plane Jet Impingement

Abstract: This paper presents experimental and numerical studies on the erosion of a horizontal granular bed by a two-dimensional plane vertical impinging jet to predict the eroded craters’ size scaling (depth and width). The simulations help understand the microscopic processes that govern erosion in this complex flow. A modified jet-bed distance, accounting for the plane jet virtual origin, is successfully used to obtain a unique relationship between the crater size and a local Shields parameter. This work develops a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Zhang et al [70] used the Wray-Agarwal turbulence model and a PIV test to study the oblique submerged impact jet at different impact heights and concluded that the impact height affects the flow field structure of the oblique jet, while the range of effective impact pressure on the wall is independent of the impact height. Damien et al [71] studied the erosion of a two-dimensional vertical impact jet on a horizontal sand bed, and concluded that under different impact distance and jet velocity conditions, the depth and width of the…”
Section: Research Of Impact Jet Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [70] used the Wray-Agarwal turbulence model and a PIV test to study the oblique submerged impact jet at different impact heights and concluded that the impact height affects the flow field structure of the oblique jet, while the range of effective impact pressure on the wall is independent of the impact height. Damien et al [71] studied the erosion of a two-dimensional vertical impact jet on a horizontal sand bed, and concluded that under different impact distance and jet velocity conditions, the depth and width of the…”
Section: Research Of Impact Jet Mechanismmentioning
confidence: 99%
“…Zhang et al [70] used the Wray-Agarwal turbulence model and a PIV test to study the oblique submerged impact jet at different impact heights and concluded that the impact height affects the flow field structure of the oblique jet, while the range of effective impact pressure on the wall is independent of the impact height. Damien et al [71] studied the erosion of a two-dimensional vertical impact jet on a horizontal sand bed, and concluded that under different impact distance and jet velocity conditions, the depth and width of the sand pit are determined by effective impact distance and dimensionless erosion parameters. At present, the mechanical research of impact jets is mainly carried out through the combination of simulation and experiment, which is conducive to promoting the development process of low-disturbance deep-sea mining equipment.…”
Section: Research Of Impact Jet Mechanismmentioning
confidence: 99%
“…Também foram realizados estudos dos efeitos da aplicação de jatos verticais de água em solos granulares, conforme [e.g. [13][14][15][16][17][18][19].…”
Section: Introductionunclassified